Not Everyone Will Be Taken into the Future? The Role of Forecasting in International Relations Theory - I. А. Istomin (Международная аналитика, 2024)
The 2010s witnessed intensified debates in international academia on the relationship between theory and forecast, but Russian scholarship remained detached from these discussions. This article intends to examine the contribution of theory to forecasting in IR, identifying prospects for combining the prescriptive, explanatory, interpretive and predictive functions of science. It reveals the origins of both theoretical skepticism about prediction and the countercriticism of futile theorizing. The article reveals the limitations of both the hypothetico-deductive model of scholarship, which dominates  the discipline, and the statistical inductivism that opposes it. The analysis begins by identifying the diﬀerent classes of theories in international relations studies. It demonstrates that the basic assumptions of normative, deconstructive, and interpretive theorizing are poorly compatible with prediction. The article further scrutinizes the ambivalent attitude of explanatory theories towards the matter, claiming the fundamental unpredictability of social interactions. It explores the growth in expectations since the late 2000s that the accumulation of big data and the advancement of methods for processing them will provide predictions without relying on explanatory inferences. Nevertheless, the value of scholarship for foreign policy practice requires a combination of theoretical explanations and predictive studies. This article suggests that for theory to play a major role in forecasting, forecasts must play a major role in theorizing. In this sense, reluctance to test their logical inferences with predictions exemplified by scholars poses a barrier to the development of IR studies.